Food Aid Airdrop Strategy in the 2025 Joint Humanitarian Operation in Gaza - Sumarna Sumarna; Thomas Thomas; Tasdik Tasdik (CV. Rayyan Dwi Bharata, 2025)
The prolonged conflict between Palestine and Israel has generated a severe humanitarian crisis, particularly in the Gaza Strip, where civilians face major difficulties in obtaining basic necessities due to the blockade and the intensity of Israeli attacks. In this context, food-aid airdrop operations have emerged as an effective alternative for reaching affected areas that are inaccessible through land routes. This study aims to analyze the strategy and operational constraints of food-aid airdrops conducted as part of the joint operation of the GARUDA Merah Putih Task Force in the 2025 Gaza humanitarian mission. The research adopts a qualitative case-study approach grounded in Arthur F. Lykke, Jr.’s strategic theory, Wassenhove’s humanitarian logistics preparedness model, and NATO’s military logistics framework. The findings indicate that the implementation of food-aid airdrops in the Gaza joint humanitarian operation involved a high level of complexity. Accordingly, the airdrop strategy was carried out through an integrated sequence of stages, encompassing planning, mobilization of personnel and equipment, execution of the drops, and post-operation evaluation and termination. The GARUDA Merah Putih Task Force successfully prepared and delivered 520 aid bundles (approximately 91.4 tons of food supplies) using the Low Cost Low Altitude (LCLA) method with a high level of delivery accuracy. Nevertheless, the operation encountered several challenges, including limited rigging equipment, shortages of qualified personnel, changes in flight clearances, and the absence of pre-deployment training. Based on these insights, the study recommends: (1) strengthening the stock of internationally standardized rigging equipment in each Army Logistics (Bekang) unit, (2) conducting internationally scaled joint training for cross-service humanitarian operations, and (3) developing TNI doctrine specifically for global humanitarian missions.